Water as the Key to Proto-Aragonite Amorphous CaCO3 - Farhadi-Khouzani, M.; Chevrier, D.; Zhang, P.; Hedin, N.; Gebauer, Denis (Wiley-VCH Verlag, 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, WeinheimTemperature and pH value can affect the short-range order of proto-structured and additive-free amorphous calcium carbonates (ACCs). Whereas a distinct change occurs in proto-vaterite (pv) ACC above 45 °C at pH 9.80, proto-calcite (pc) ACC (pH 8.75) is unaffected within the investigated range of temperatures (7–65 °C). IR and NMR spectroscopic studies together with EXAFS analysis showed that the temperature-induced change is related to the formation of proto-aragonite (pa) ACC. The data strongly suggest that the binding of water molecules induces dipole moments across the carbonate ions in pa-ACC as in aragonite, where the dipole moments are due to the symmetry of the crystal structure. Altogether, a (pseudo-)phase diagram of the CaCO3 polyamorphism in which water plays a key role can be formulated based on variables of state, such as the temperature, and solution parameters, such as the pH value.